Penerapan Program Inkubasi sebagai Program Baru untuk Pembinaan Awal Peserta Didik Dengan Strategi Business Model Canvas (BMC) (Studi Kasus di Bestfriend Education Management (BEM)) Implementation of Incubation Program as A New Program for The First Coach - Hastiyan, Dedy; Arum, Khorifah; Kumuda, Raharja Tri (EBBANK, 2024)
Many inconsistencies in understanding English and mathematics materials that occur in several study groups for elementary and junior high school students, both new and old students at the Bestfriend Education Management (BEM) after the pandemic, cause teaching and learning activities that occur to be inefficient because in one group the teacher will divide into groups that already understand and those that do not understand. Even though the group has been divided according to the class and level of each school. So it takes a new program using a business design to be able to equalize this inconsistency. The new program that was created is called an incubation program. The purpose of creating this program is to find out how to create, design and implement the new program into the operational business of the institution's educational services so that it can have the impact expected by all parties. This business design was carried out at Bestfriend Education Management (BEM) which is located in Dsn. Tado Ds Singkalan RT 04 RW 03 Kec. Balongbendo Kab. Sidoarjo, East Java on April 5, 2023-April 30, 2024. The method used in making this business design is a qualitative case study method using data collection techniques through observation, interviews, and Focus Group Discussions (FGD) and using the Business Model Canvas (BMC) strategy. The results of the implementation of this incubation program business design have proven to be able to help institutions solve problems of differences in understanding that occur in the classroom, make effective and efficient learning and also become an advantage for institutions compared to other institutions with this new program.